Aromatic stability of Syrah and Petit Verdot tropical wines from Brazil. - ARAÚJO, A. J. de B. (2012)
The production of fine wines in the Sub-middle of the São Francisco River Valley, Northeast of Brazil, is relatively recent, about twenty-five years ago. This region presents different characteristics, with a tropical semiarid climate, in a flat landscape. Presenting high annual average temperature, solar radiation and water in abundance for irrigation, it?s possible the scaling the grape harvests for winemaking throughout the year, allowing to obtain until two harvests per year. Several factors may affect the aromatic compounds in wines, such as viticulture practices, climatic conditions, cultivars and winemaking process. This study aimed to evaluate the aromatic stability of Syrah and Petit Verdot tropical wines elaborated in two different periods in the year. The grapes were harvested in the first and second semesters of 2009, in June and November. The wines were elaborated and then, they were bottled and analyzed in triplicate, thirty days and one year after bottling, by gas chromatography with ionization detector flame (GC-FID), to evaluate the profile and the stability of the aroma compounds. Principal component analysis was applied to discriminate between wine samples and to find the compounds responsible by the variability. The results showed that Syrah and Petit Verdot tropical wines presented different responses, for stability of higher alcohols, esters and carboxylic acids.